PERAN KOMISI PENYIARAN INDONESIA DAERAH SUMBAR DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KONTEN PORNOGRAFI - Nuriya Ulva; Sukmareni Sukmareni; Riki Zulfiko (Ensiklopedia of Journal, 2023)
The Indonesian Broadcasting Commission (abbreviated as KPI) is an independent institution in Indonesia whose position is at the same level as other state institutions that functions as a regulator of broadcasting operations in Indonesia. KPI also has the authority to formulate and supervise various broadcasting regulations that link broadcasters, the government and the public. Those who found violations of broadcast content on a television and radio program. The purpose of this study was to find out the role of the West Sumatra KPID in providing legal protection for child victims of pornographic content, to find out the obstacles and efforts made by the Indonesian Broadcasting Commission in providing legal protection for child victims of pornographic content.The research conducted is empirical legal research, which is legal research that examines law which is conceptualized as real behavior as a social phenomenon that is unwritten in nature in examining problems seen in terms of the rule of law regarding the role of the Indonesian Broadcasting Commission in the West Sumatra region in providing protection for children from pornographic content. the data used are primary and secondary data, which are obtained directly from KPID as respondents and informants, as well as resource persons. And secondary data. The data collection method used in this study is empirical research. The data analysis used is qualitative dataBased on the research results it is understood that the role of KPID in providing legal protection for child victims of pornographic content is to accommodate aspirations and represent the interests of the community, KPI is tasked with ensuring the implementation of a sound and quality broadcasting system. The constraints of the Indonesian Broadcasting Commission on broadcasting institutions broadcasting pornographic content are that the regulation on KPI in the Broadcasting Law is inadequate for KPI in carrying out its functions, duties and authorities, KPI institutions are not yet ideal, where KPI is still coordinative which causes many problems in imposing sanctions and KPI financing and other constraints, namely that the KPID has not been able to implement laws and regulations to the fullest. KPI's efforts in tackling broadcasters broadcasting pornographic content are to comprehensively regulate the formation of KPI institutions. Changing the institutional structure of KPI with KPID which was originally coordinative to hierarchical. In addition, it is also necessary to clearly regulate the legal instruments that can be used by KPI in carrying out its functions, duties and authorities.